[tex]a)3(x+2)^{2} -(x-1)^{2} +2(x-3)(x+3)= \\ 3(x^{2} +2x+4)-(x^{2} -2x+1)+2(x^{2} +3x-3x-9)= \\3 x^{2} +6x+12- x^{2} +2x-1+2 x^{2} -18= \\ =4 x^{2} +8x-7 \\b) (\frac{2x-1}{2})^{2}+(3x+1)^{2} -( \frac{2}{3x-5})( \frac{2}{3x+5} ) \\ \frac{4 x^{2} -2x+1}{4} +9 x^{2} +6x+1- \frac{4}{ 9x^{2}-25 } \\ \\ c ^)(4x-y) ^{2}+(2x-5y)(2x+5y)-3(3x+y)^{2}= \\ 16 x^{2} -8xy+y^{2}+4 x^{2} -25y^{2} -3(9 x^{2} +6xy+y^{2})= \\ 16 x^{2} -8xy+y^{2}+4 x^{2} -25y^{2} -27 x^{2} -18xy-3y^{2} = \\7 x^{2} -26xy-27 ^{2}[/tex]